Real Steel Custom (RSC) Sdn Bhd - Juhimin, Shahrul; Hamjah, Mohd Khairil; Abduh, Mohd Syuwari; Ladso, Roynold Eddie; Saunin, Sazuneh (2014)
REAL STEEL CUSTOM (RSC) SDN BHD is a business that is establish in order to fulfil the needs of a quality and reasonable price for those that needs to customize their car. This business provide not only provides service for customizing car but also selling an accessory to customer. Our business developed its business plan in order to attract attention for any potential investor, such a bank to easier our loan process. Our business consideration is to attract many customers in order to compete with the existing service. In our business, there will be five persons who leads the main departments and each of those person expertise in the field of that segment of department thus it is can aid for the business to run smoothly. Those five persons also a partners to the business which every person contribute their capital since this business established in the form of partnership. We have provide a specific location for our business operation that is suitable to attract more consumer and gives a more contact efficient to our potential user or consumer to gives our service a try. We have fully analyse our business and provide a strategies by develop our business plan and provide a budget for main department in order to encounter any possibility that occur when the business start run. Our business will success and can compete with an existing business.